Social Media as Predictor of Job Search Skills among Undergraduates of Obafemi Awolowo University, Ile-Ife, Osun State, Nigeria - Tolulope Francisca, Agun; Adeola Olusegun, Atoyebi (American Economic & Social Review, 2020)
The study investigated the level of job search skills among undergraduates of Obafemi Awolowo University, Ile-Ife Osun state and determined the predictive ability social media on job search skills. It examined the influence of the social media on job search skills of undergraduates of the university, Further, it investigated the influence of demographic variables (sex, age and level) and area of specialisation on job search skills of the undergraduate students. These were with a view to providing information on the factor that could improve the job search skills of O.A.U undergraduate students.The study adopted a descriptive survey research design. The population for the study comprised 26,000 undergraduates of the Obafemi Awolowo University, Ile-Ife, Osun State as at 2016/2017 academic session. The study sample comprised 496 students were selected using a multi-stage sampling procedure. Out of the thirteen faculties, four faculties were selected using simple random sampling technique. Four departments were selected from each of the selected faculties using simple random sampling technique. Purposive sampling technique was used to select graduating students (Parts 4 or 5) from each of the faculties selected. One hundred and twenty-five undergraduates were selected from each faculty, using convenience sampling technique. An instrument titled “social media of Job Search Skills” was adapted from existing standardised instruments and used to collect data. Data collected were analysed using percentage, frequency counts, mean, standard deviation, linear regression, and ordinal logistic regression.The result showed that 21.4%, 55.6% and 23.0% of undergraduates of Obafemi Awolowo University students demonstrated low, moderate and high levels of job search skills respectively. Also, the predictive ability of social media showed that social media (0.323, p< 0.000) had a significant influence on students’ job search skills. The study concluded that social media could improve the job search skills among undergraduates of OAU.